Modelling of carbon sequestration potential in rubber tree (hevea brasiliensis) saplings and plantations in Malaysia / Engku Azlin Rahayu Engku Ariff - Engku Ariff, Engku Azlin Rahayu (2017)
The climate change and global warming occurred due to excessive build-up of greenhouse gases (GHGs) especially CO2 in the atmosphere. In order to stabilize the GHGs, the forest has to be conserved because the terrestrial ecosystems are vital carbon sink that store large amount of atmospheric CO2. Rubber plantation is manmade forest and is classified as forest plantation. In the Southeast Asia, increasing demand on natural rubber and rubber wood industry are factors that contribute to the expansion of rubber plantations which is predicted to replace the secondary forests in 2050.